(untitled) (Marketing Journal, 2025)
The article examines economic security in the formation and development of clusters of the manufacturing industry. Clusters are an association of interconnected enterprises, scientific institutions and infrastructure facilities, which contributes to increa sing the competitiveness and sustainability of the economy. However, without effective mechanisms for ensuring economic security, clusters may face risks that affect their development.